Aplikasi Media Pembelajaran Olahraga Bola Basket Menggunakan Adobe Flash - Khairunnisa Khairunnisa (Program Studi Sistem Informasi, 2019)
The development of information technology is currently very rapid. So that it influences the world of education, especially in the learning media. Every student has different abilities and ways of thinking to develop themselves in understanding a material. One of them, when studying Basketball Sports Materials. This application is made to help educators to be more efficient in teaching so that students are able to learn and understand the material techniques available in basketball sports through learning media applications with Adobe Flash. So that students can learn wherever and whenever. With the existence of this Basketball Sports Learning Application, it is expected to be able to provide material that is easier in understanding, interactive in teaching, interesting in giving material to students, and can facilitate the teaching and learning process in Basketball Sports practice to users.Keywords: Application, Learning Media, Basketball, Adobe Flash